Sustainability performance, corporate governance, and financial performance: Evidence from Poland and Central European listed companies - Joanna Błach; Elżbieta Bukalska; Bogna Kaźmierska-Jóźwiak; Anita Radman Pesa (Journal of Entrepreneurship, Management and Innovation)
PURPOSE: Businesses are regarded as the main agents that can help achieve sustainable development. Therefore, more and more firms of various characteristics integrate sustainability issues into their business strategies. There is ongoing debate on the relationship between sustainability engagement and firm performance, with ambiguous results. Our study falls into this stream of research by adding the perspective of the Central European economy. The main objective of our paper is to examine the relationship between firm sustainability performance and its financial performance in the context of various corporate governance characteristics (in particular board attributes and ownership structure). METHODOLOGY: Our research sample covers firms listed on the Warsaw Stock Exchange representing various indexes (related to their size) and sectors in 2015–2021. We measure sustainability performance with our original aggregated index created by integrating key firm ESG engagement characteristics. Financial performance is analyzed from two different perspectives – accounting perspective illustrated by profitability of assets (ROA) and market perspective - illustrated by market value (MV/BV ratio). To achieve the research aims, several statistical methods were employed in the study, including selected descriptive statistics and panel regression models. FINDINGS: Our results confirm a significant positive relationship between sustainability and financial performance, as measured by ROA and MV/BV ratios. Additionally, we observe a significant positive relationship between gender diversity on the management board (the presence of women on the management board) and accounting performance. Our results provide an argument for firm engagement in sustainability initiatives, as it may improve its profitability and market value. IMPLICATIONS for theory and practice: Our study not only contributes to the corporate finance and sustainability literature by providing evidence on the relationship between sustainability performance and financial performance in the context of the Central European economy, but also provides insights for corporate governance research in terms of boards attributes and different types of ownership structures. The policy suggestions derived from our findings can benefit both managers and regulators, focusing on the sustainable development paradigm and ultimately enhancing overall stakeholder well-being. ORIGINALITY AND VALUE: The originality of our research stems from investigating the relationship between sustainability performance and firm performance from both an accounting and a market perspective and using the original sustainability index developed for the purpose of the study. Additionally, we address potential gaps in existing research by incorporating several corporate governance characteristics to clarify their importance for a firm performance.